Expérimentations d'hibernation de quelques espèces de mugilides en conditions de laboratoire - Udrea, Valerian (Cercetări Marine - Recherches Marines, 2026)
The paper presents the experimental results on winter passing of 3 mullet species (Mugil cephalus. M. auratus and M. saliens) during 1972-1973 winter. The experiments pointed out the temperature ranges to keep ensuring an optimum survival. Sometime the experiments allowed knowledge on the populations densities per cubic meter to be considered on designing the winter passing basins.